2016
DOI: 10.1016/j.virol.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

CD4 + T cells require either B cells or CD8 + T cells to control spread and pathogenesis of a neurotropic infection

Abstract: Immunity within the brain, specifically to virus-infected neurons, must be controlled to prevent neuron loss and impairment, though the process by which this occurs remains unclear. Here, we use a mouse model of neuron-restricted measles virus infection, in which immunocompetent adults survive challenge, whereas T and B cell-deficient mice succumb. This model allowed us to more precisely define the contributions of CD4+ T cells, CD8+ T cells, and B cells in neuroprotection. Both B cell knockout mice and mice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Both T cells and IFNγ are critical to the survival of adult CD46+ mice. CD46+ adult mice lacking mature T and B cells (CD46+/RAG2-KO) experience 100% mortality during infection, whereas CD46+ adult mice lacking only B cells do not succumb to the infection (Solomos et al, 2016). CD46+ adult mice that lack IFNγ (CD46+/IFNγ-KO) do not clear the virus, with ~50% of the mice succumbing to the infection within 21 dpi (O’Donnell, Conway, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Both T cells and IFNγ are critical to the survival of adult CD46+ mice. CD46+ adult mice lacking mature T and B cells (CD46+/RAG2-KO) experience 100% mortality during infection, whereas CD46+ adult mice lacking only B cells do not succumb to the infection (Solomos et al, 2016). CD46+ adult mice that lack IFNγ (CD46+/IFNγ-KO) do not clear the virus, with ~50% of the mice succumbing to the infection within 21 dpi (O’Donnell, Conway, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…While there is a role of type I IFNs in limiting viral replication in neurons, there are open questions about the mechanisms used by T cells to target these cells. For example, the non-cytolytic clearance of Measles (the cause of sub-acute sclerosing panencephalitis) and Sindbis from neurons is IFN-γ dependent ( Binder and Griffin, 2001 , Patterson et al., 2002 ) and there appears to be a bystander role for CD4 + T cells in some of these events ( Solomos et al., 2016 ). In “carrier mice” that have an established LCMV infection in neurons, there is a literature that identifies “therapeutic” CD8 + T cells as being important in elimination of this virus pool through the production of IFN-γ that licenses microglia to purge virus, present antigen, and amplify the local antiviral T cell response ( Herz et al., 2015 , Oldstone et al., 1986 , Pinschewer et al., 2010 ).…”
Section: Main Textmentioning
confidence: 99%
“…Studies using the herpesviruses VZV and HSV have shown that T rm lymphocytes are necessary to maintain viral latency (14-21, 23, 30). Considering that T cells are paramount for controlling acute neuronal MV infection in our model (31,32), coupled with the knowledge that T rm lymphocytes prevent viral RT-qPCR data were generated using randomhexamer priming for cDNA generation, followed by qPCR using primers specific for the MV nucleoprotein and cyclophilin B as a standard. Data were analyzed using the ΔΔC T method.…”
Section: Nse-cd46mentioning
confidence: 99%